PENGEMBANGAN BAHAN AJAR STATISTIKA BERBASIS INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) - Suryani Lukman, Hamidah; Sutisnawati, Astri (Universitas Wiralodra, 2016)
This paper is the research and development result of Statistics teaching materials based on ICT. The method used is the early stage of research and development that applied on the second phase of the study. The first stage is analysis the teaching materials through the study of literature; developing initial products; experts team validation; and first revised. The second phase is limited test to 13 students randomly selected that participated in the course Statistics on Mathematics Education Universitas Muhammadiyah Sukabumi, and do the second revised. The method used in the second stage is a single experiment one shot case study. The instrument used in this study are validation sheet, teaching materials performance and effectiveness sheet, and conceptual understanding test. These data were analyzed using descriptive analysis and Wilcoxon Signed Ranks Test on the level of α = 5%. The results showed that average score of teaching materials validation is 4.50 out of This result indicates that more than 80% of ICT based teaching materials developed is feasible to use (valid) and classified as very well category. Based on trial results, conceptual understanding ability of students after using ICT based teaching materials significantly better than before using ICT based teaching materials. In addition, an overall assessment of performance effectiveness of ICT based teaching material reached 62.98% higher than the learning without ICT based teaching materials, which only reached 60.58%. These results indicate that using ICT based teaching materials in learning has the valid, practical, and effective criteria, particularly in an effort to develop the students’ conceptual understanding ability.